The Rockefeller Foundation, John Marshall and the Development of the Humanities in Modern Turkey: 1950–1965 - (:unkn) unknown (My University, 2015)
Bu makale Rockefeller Vakfı’nın 1950 ile 1965 yılları arasında Türkiye’deki beşerî bilim faaliyetlerine katkısını analiz etmektedir. John D. Rockefeller’ın 1913’te kurduğu vakıf sağlık ve sosyal bilim faaliyetlerine yoğunlaşıp rasyonel bilgi dağarcığını zenginleştirip “bilimsel” kültürü güçlendirmeyi amaç edinmişti. Ancak bilim ve teknolojideki ilerlemenin insanlığın mutlak faydasına olmadığı İkinci Dünya Savaşı’ndaki yıkım ile anlaşılmış, sosyal bilimlerin de insan davranışlarını kontrol etmede yetersiz kaldığı görülmüştü. 1945 sonrası kendine yeni yol haritası arayan vakıf yönetimi bu sorunların çözümü için beşerî bilimlerin geliştirilmesi ve desteklenmesi gerektiği sonucuna vardı. Soğuk Savaş dönemi Amerikan çıkarları için önemli bir ülke olan Türkiye giderek vakfın ilgi alanına girdi. Aslında Türkiye 1945 öncesinde Rockefeller Vakfı tarafından sağlık hizmetleri alanında destek alan bir ülkeydi, ancak 1950– 1965 yılları arasında beşerî bilimler alanındaki destekler önem kazandı. Rockefeller Vakfı’nın Türkiye’deki faaliyetleri için anahtar şahsiyet vakfın beşerî bilimler biriminin direktör yardımcısı John Marshall’dır. 1948–1960 yılları arasında Türkiye’yi sık sık ziyaret eden Marshall edebiyat ve sanat erbabı ile sık sık görüştü; bürokrasi ve okul yö- neticileri ile dostluk geliştirdi. Marshall’a göre İslam Yakın Doğu’da şaşırtıcı bir şekilde gücünü korumaktaydı ve bu bölgede yaşanacak sosyal değişim yabancı değil yerli aktörler tarafından gerçekleştirilecekti. Marshall Türk toplumunu kabaca “nüfuz edilemeyen çoğunluk” ve “yaratıcı azınlık” olarak ikiye ayırıyor, Türkiye’nin batıya yakınlaşmasının ancak kendileriyle aynı vizyonu paylaşan “yaratıcı azınlık” eliyle sağlanabileceğini iddia ediyordu. Ona göre, Rockefeller Vakfı gibi Batılı kurumlara düşen görev bu değişime liderlik edecek isimleri tespit edip kendi ülkelerinde önlerini açmaktır. Vakfın Türkiye’deki faaliyetleri Marshall’ın çizdiği bu çerçeveye göre şekillendi. Zamanın aydın çevreleri nezdinde ilgi uyandıran ve revaç bulan Rockefeller destekleri Türk batılılaşmasının yönünü tayinde kayda değer bir rol oynamıştır.

This article examines the involvement of the Rockefeller Foundation in the realm of the humanities in Turkey between 1950 and 1965. John D. Rockefeller founded the Rockefeller Foundation in 1913. Focusing on medicine and social sciences, the foundation aimed to enrich “scientific culture” and support the pursuit of scientific knowledge. The scale of the destruction during the Second World War, however, showed that scientific and technological progress was not necessarily beneficial for humanity and revealed that the social sciences were an insufficient means of understanding and governing human behavior. In its search for a new approach in the aftermath of the war, the administration of the foundation came to the conclusion that the development and support of the humanities could aid in addressing these failures. As a country of strategic importance for American interests during the Cold War, Turkey increasingly drew the attention of the foundation. While Turkey had received some Rockefeller support before 1945, mostly in the field of health, between 1950 and 1965 the foundation’s growing support for projects in the country increasingly focused on the humanities. The key person in the foundation’s activities in Turkey was John Marshall, vice-director of its Division of Humanities. During his frequent visits to Turkey between 1948 and 1960, Marshall met and befriended bureaucrats, school administrators, and men of arts and literature. According to Marshall, Islam maintained a surprising hold in the Near East, and he believed that for this reason only locals, not foreigners, could be the vanguards of future social change in the region. Marshall divided Turkish society into two rough groups: the “impregnable majority” and “creative minority,” claiming that Turkey’s rapprochement with the West could only be achieved by the “creative minority” who shared its vision. For him, the duty of western organizations like the Rockefeller Foundation was to identify members of the creative minority and support their activities locally. In the following years, this framework shaped the activities of the foundation in Turkey. Rockefeller grants quickly became in high demand among the Turkish intelligentsia and left a serious impact on the direction of Turkish Westernization.
Rockefeller Vakfı, John Marshall ve Modern Türkiye’de Beşerî Bilimlerin Gelişimi:1950–1965